Kasr AL-Ainy's psoriasis unit protocol for the treatment of psoriasis, part II: biological therapies - Hoda Rasheed; Hesham A.Z AEl-Moaty; Mohamed H.M El-Komy; Heba Mashaly; Khadiga S Sayed; Vanessa Hafez; Marwa S El-Mesidy; Eman R Said; Marwa A Amer; Aya M AlOrbani; Dina G Saadi; Mona El-Kalioby; et al. (Wolters Kluwer Medknow Publications, 2019)
Psoriasis is a chronic multisystem inflammatory disease affecting primarily the skin and joints but also involves several comorbidities. The disease affects between 0.2 and 4% of the population worldwide. The Kasr Al-Ainy Psoriasis Unit developed a protocol of therapy for psoriasis. Part I discussed the topical and systemic therapies. This part discusses the biological therapy. Biological therapies for psoriasis are agents that can specifically target an immune mediator and block specific molecular steps important in the pathogenesis of psoriasis. Despite the cost, the use of biological therapies in psoriasis is sometimes necessary. However, the adequate choice of biologic in the proper indication is mandatory for cost-benefit balance for the patient. Physicians using biological therapies should be familiar with complications. The protocol offers regional physicians a practical algorithm for choice of biological therapies in psoriasis and a full workup before therapy and during follow-up. Authors highlight the safety and efficacy data of biologic therapies available in the Egyptian market, with special focus on particular situations (hepatitis, tuberculosis, and demyelinating disorders).